2021
DOI: 10.3389/fpsyg.2021.661208
|View full text |Cite
|
Sign up to set email alerts
|

Parental Beliefs and Knowledge, Children’s Home Language Experiences, and School Readiness: The Dual Language Perspective

Abstract: Parental beliefs and knowledge about child development affect how they construct children’s home learning experiences, which in turn impact children’s developmental outcomes. A rapidly growing population of dual language learners (DLLs) highlights the need for a better understanding of parents’ beliefs and knowledge about dual language development and practices to support DLLs. The current study examined the dual language beliefs and knowledge of parents of Spanish-English preschool DLLs (n = 32). We further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
2
9
0
Order By: Relevance
“…However, some teachers expressed giving recommendations for language use based on the misperception that using two languages in one setting is problematic. This is similar to what has previously been demonstrated in both kindergarten and primary school teachers (Strobbe et al, 2017) and parents of DLLs (Luo et al, 2021). In addition, the qualitative results also demonstrated that no teacher mentioned the centre's role in improving parent collaboration, indicating a potential for the ECEC centre to support their teachers and parents to communicate and collaborate.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, some teachers expressed giving recommendations for language use based on the misperception that using two languages in one setting is problematic. This is similar to what has previously been demonstrated in both kindergarten and primary school teachers (Strobbe et al, 2017) and parents of DLLs (Luo et al, 2021). In addition, the qualitative results also demonstrated that no teacher mentioned the centre's role in improving parent collaboration, indicating a potential for the ECEC centre to support their teachers and parents to communicate and collaborate.…”
Section: Discussionsupporting
confidence: 86%
“…Still, there are indications of a need for parental support regarding dual language development. For instance, Luo et al (2021) reported that parents tended to misperceive characteristics of dual language development, such as codeswitching, as indicators of problem or disadvantage. Similar misperceptions of languages as fixed entities which should not intermingle in practice were also found in kindergarten and primary school teachers (Strobbe et al, 2017).…”
Section: Teacher-parent Collaboration To Support Language Developmentmentioning
confidence: 99%
“…Once we take resources into account, the statistical significance of advice from other sources increases, but the effect size remains weak. Families with more resources might know better where to find accurate or nuanced advice and might find it easier to follow this advice (Luo et al, 2021; Rowe et al, 2016). Interestingly, the bivariate analysis uncovers a moderately strong positive significant correlation between the two sources of advice.…”
Section: Discussionmentioning
confidence: 99%
“…Kim and Starks 2010), (mis) conceptions about (bilingual) language acquisition (e.g. Luo et al 2021), children's agency (e.g. Kheirkhah and Cekaite 2015;Tuominen 1999), (teacher) advice (e.g.…”
Section: Institutional Language Exposurementioning
confidence: 99%
“…Besides, the (un)solicited advice on multilingual childrearing proffered by early childhood professionals (e.g. childcare workers, paediatricians), teachers, speech therapists, relatives, popular parenting literature, websites and online discussion forums, however, should not be overlooked as another important basis for how families mould their linguistic environment (Bezcioglu-Goktolga and Yagmur 2018; Kaveh 2017; King and Fogle 2006;Luo et al 2021;Piller and Gerber 2021). The advice given by teachers and other professionals is likely to be shaped by the institutional context in which they operate.…”
Section: Advicementioning
confidence: 99%